Kualitas Audit, Kondisi Keuangan, Ukuran Perusahaan dan Penerimaan Opini Audit Going Concern - Bahtiar Effendi (Owner : Riset dan Jurnal Akuntansi, 2019)
This study aims to analyze the quality of audits, financial condition and firm size on audits that occur in companies listed on the Indonesia Stock Exchange period 2014-2016. The population of this research is all transportation company in Indonesia year 2014-2016. The number of samples were 14 transportation companies, selected using purposive sampling method. This study uses data collected from Indonesia Stock Exchange (BEI) in 2014-2016 and also from each company website. By using multiple analysis as the method and result of this research, deep audit can be done.